Effect of teacher’s performance in the implementation of environmental education to the student’s active participation in maintaining environmental sustainability - Kristalinawati Kristalinawati; Suyud Warno Utomo; Tri Edhi Budhi Susilo (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2019)
Environmental education (EE) has begun in Indonesia since 1970, however the environmental damages that come from human behaviour are still going on and even increasing. This may imply that the results of environmental education have not been seen. Performance of teachers as educators and learning designers need to be evaluated. The research was conducted at Gonzaga High School in Jakarta and Loyola High School in Semarang with a quantitative approach and qualitative data as supporters. The method used was survey, with questionnaires technique and in-depth interviews. The results show that the active participation of the students in terms of protecting the environment is very low. It means the effectiveness of environmental education in terms of this side is not effective. Performance of teachers as educators and learning designers in the implementation of EE affects the active participation of students in terms of conserving the environment. Training for teachers in making learning instrument needs to be done regarding the conduct of learning related EE more effective.